Utilizing Quality Improvement Processes to Reverse the Rising Trends of Cesarean-Section Births [30J]. (May 2016) - Ogunyemi, Dotun; McGlynn, Sara; Leahy, John; Knudsen, Patricia; Redman, Mark; Bahado-Singh, Ray
Abstract : INTRODUCTION: To report on quality processes aimed at decreasing primary C/S rates and Perinatal Core Measure 2 (PCO2): C/S in term singleton vertex nulliparous pregnancies. METHODS: From May 2014, processes included: 1) review of local risk factors; 2) Provider education; 3) Kaizen to implement minimum duration of labor calculations; 4) C/S Committee reviews utilizing ACOG/SMFM guidelines with feedback to obstetricians; 5) Daily benchmarked C/S rates for awareness; 6) providers' surveys on attitudes & potential opportunities; 7) serial C/S rates score cards distribution; 8) monitoring safety committees; 9) C/S checklist; 10) Patient education including safe labor brochures; 11) nursing focus on natural labor, bedside care, and positional changes; 12) residents as a focus of change. Primary outcomes were primary C/S and PCO2 rates; secondary outcomes included operative vaginal deliveries, postpartum hemorrhage (PPH), chorioamnionitis, perineal trauma and perinatal mortality rates. United Health Consortium upper quartile average was the benchmark. RESULTS: U-chart analysis of individual physician primary C-S rates was within control limits demonstrating that the C/S rate was due to culture and not "outliers." From April 2014 to July 2015, primary C/S decreased significantly from 22.5% to 13.9%, and PCO2 from 38.98% to 17.29% There were no significant trends in forceps deliveries: 2.4% to 1.4%; vacuum deliveries: 3.7% to 1.1%; chorioamnionitis 0.7% to 0.2%, PPH: 3.4% to 2.4%, non-instrumental perineal trauma: 1.7% to 1.75%, or instrumental perineal trauma: 20% to 35.7%. CONCLUSION: Quality processes can result in safe reduction of the primary C/S rate by a focus on "natural labor" with patience without increasing co-morbidity.